2011
DOI: 10.1186/1471-2458-11-309
|View full text |Cite
|
Sign up to set email alerts
|

Weight changes and lifestyle behaviors in women after breast cancer diagnosis: a cross-sectional study

Abstract: BackgroundWeight gain rather than weight loss often occurs after breast cancer diagnosis despite breast cancer survivors frequently reported making healthful lifestyle changes. This study describes the prevalence and magnitude of changes in weight before and after breast cancer diagnosis and examines lifestyle behaviors of breast cancer survivors with stable weight, weight gain or weight loss.MethodsRespondents were 368 women with breast cancer characterized by stages I, II and III. All were recruited from hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
1
34
3
Order By: Relevance
“…This result is not supported by those of other studies (Kacem et al, 2010;Yaw et al, 2011). The majority of participants in this study had an acceptable BMI.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This result is not supported by those of other studies (Kacem et al, 2010;Yaw et al, 2011). The majority of participants in this study had an acceptable BMI.…”
Section: Discussioncontrasting
confidence: 54%
“…Other critical factors associated with breast cancer include stress, hormone therapy, genetics, environmental, diet, aging, smoking, alcohol, lack of exercise, that cause of breast cancer (Stewart et al, 2001;Wang et al, 2010;Ferrucci et al, 2011;Panjari et al, 2011). Numerous studies have shown that almost half of the women studied had abnormal BMI during the year preceding their breast cancer diagnosis (Kacem et al, 2010;Litton et al, 2011;Yaw et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During the period of interviewing, the HCPs used the Dutch breast cancer guidelines for breast cancer care in hospitals [39], and for GPs [33]. These guidelines, and also the guidelines used in the UK and US [42,43], do not include information on weight gain as adverse effects of chemotherapy, despite growing evidence [7][8][9][10][11]. In the new Dutch guidelines 2017, involuntary weight gain (BMI > 25; weight gain >5% or > 3 kg since diagnosis; middle waist > 88 cm) is now included, but only in the diagnostic phase not during treatment [44].…”
Section: Discussionmentioning
confidence: 99%
“…Over 60% of women with breast cancer receive (neo) adjuvant chemotherapy [2]. Several studies reported that chemotherapy is associated with weight gain [7][8][9][10][11]. Weight gain may have long-term consequences because it can lead to a higher risk of developing cardiovascular disease, diabetes and disease recurrence in survivors of breast cancer [12][13][14][15], and at least half of the patients experience unhappiness concerning their body changes and altered physical appearance, which negatively affected their quality of life [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…About previous research on the lifestyles of breast cancer survivors, were described as follows. Yaw et al (2011) examined 368 women with breast cancer, discovering thatmean weight change from a year past diagnosis to study access were 2.73 kg. In fact, previous studies have investigated the healthy lifestyles of breast cancer survivors regarding quality of life and adaption (Kreitler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%